The level of public acceptance of vaccine booster shot / Abdul Rauf Ridzuan … [et al.] - Ridzuan, Abdul Rauf; Mohamad Nasir, Muhammad Dannish Farish; Harni Zainal, Hani Suraya; Samsuddin, Muhammad Juffri; Hasnan, Harits Aysraf (Faculty of Communication & Media Studies, 2022)
Vaccine booster shot is an additional COVID-19 vaccine dose given to a person who has already received two COVID-19 immunizations. The goal of a COVID-19 booster is to protect those who have been fully vaccinated against COVID-19, especially from severe symptoms and, in some circumstances, death. However, over time, this protection becomes less effective. As a result, a booster is administered to improve the protection. Although a booster is not required, it is strongly advised to have one to ensure the best protection against COVID-19 infection, particularly from severe symptoms and, in some cases, death. The number of people that have already received vaccination is increasing day by day. However, mild arm discomfort, a headache, and body pains plagued one of the patients. Mild weariness and achiness were mentioned by two of the participants. One of them had a headache. Not knowing that the vaccine has mild side effects towards our body such as fever and headache, people still take the vaccine shots eventually thanks to the effort of campaigns by the government. Those side effects are affecting the emotion of the public until their faith in vaccination fades away slowly. The aim of this study is to determine the level of public acceptance of vaccine booster shot and the level of public trust in vaccine booster shot. The study is using a quantitative method through Google Form platform involving 400 respondents from various backgrounds. The result shows that most of the respondents are accepting the booster dose vaccination. (M=3.35). The level of public acceptance is very high (M=3.36) and the level of public trust of vaccine booster shot is also high (M=3.34).